Development of a Validated Chromatographic Method for Determination of Repaglinide from in vivo Study Samples for Pharmacokinetic Application - Navamanisubramanian, Raja; Panchagiri, Sabitha; Nerella , Raghunandan; Seetharaman , Shanmuganathan (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
The study was focused to develop a simple and sensitive bioanalytical method for Repaglinide in rabbit plasma towards pharmacokinetic study. The method was developed in RP-HPLC with C18 (2) analytical column \((5 \mu, 250 \times 4.6 \mathrm{~mm})\) using Acetonitrile:0.05%Trifluroacetic acid in water (55:45, v/v) as mobile phase at flow rate of 1 mL/min. The retention time of Repaglinide and Rabeprazole was found at \(\sim 4.3 \text { and } 5.1 \mathrm{~min}\) respectively, with adequate system suitability parameters. The approach is linear throughout a concentration range of 10 to 1000 ng/mL(r2=0.9987). The results of accuracy (\(\geq\) 98.17%), intra-, inter day precision (\(\leq\) 2.9%),recovery (101.21±2.09%), process efficiency (99.77±3.74%) were found satisfactory and no matrix effect. The analyte in samples was found to be stable for up to 6 hours, 3 freeze-thaw cycles, and not more than 2 months in bench-top, short, and long term stability investigations. The pharmacokinetic parameters (Cmax-139.33 ng/mL; Tmax-0.763; h KE-0.540 h-1;Ka-2.548 h-1; T1/2-1.22 h; \(\mathrm{AUC}_{0-\infty}-378.1 \mathrm{ng}{}^{*}\mathrm{~h} / \mathrm{mL} ; \mathrm{AUMC}_{0-\infty}-874.67 \mathrm{ng}^{*} \mathrm{~h}^{2}/\mathrm{mL}\) MRT-2.32 h; Vd-18.69 L; CLT-10.6 L/h) were studied from time dependent plasma concentrations of Repaglinide estimated after 4 mg oral dosing in New Zealand white rabbit. The developed bioanalytical method was selective and sensitive for the pharmacokinetic study of Repaglinide in rabbit.